Sea-ice thermodynamics can determine waterbelt scenarios for Snowball Earth - Johannes Hörner (Department of Meteorology and Geophysics, Faculty of Earth Sciences, Geography and Astronomy, University of Vienna); Aiko Voigt (Department of Meteorology and Geophysics, Faculty of Earth Sciences, Geography and Astronomy, University of Vienna) (Earth System Dynamics, 2024)
The abstract is available here: https://uscholar.univie.ac.at/o:2082887 The abstract is available here: https://uscholar.univie.ac.at/o:2082887